Effect of soil microorganisms and labile C availability on soil respiration in response to litter inputs in forest ecosystems: A meta‐analysis. Issue 24 (31st October 2020) - Zhang, Yanjun; Zou, Junliang; Meng, Delong; Dang, Shuina; Zhou, Jinhong; Osborne, Bruce; Ren, Yuanyuan; Liang, Ting; Yu, Keke
Abstract: Litter inputs can influence soil respiration directly through labile C availability and, indirectly, through the activity of soil microorganisms and modifications in soil microclimate; however, their relative contributions and the magnitude of any effect remain poorly understood. We synthesized 66 recently published papers on forest ecosystems using a meta‐analysis approach to investigate the effect of litter inputs on soil respiration and the underlying mechanisms involved. Our results showed that litter inputs had a strong positive impact on soil respiration, labile C availability, and the abundance of soil microorganisms, with less of an impact related to soil moisture and temperature. Overall, soil respiration was increased by 36% and 55%, respectively, in response to natural and doubled litter inputs. The increase in soil respiration induced by litter inputs showed a tendency for coniferous forests (50.7%)> broad‐leaved forests (41.3%)> mixed forests (31.9%). This stimulation effect also depended on stand age with 30‐ to 100‐year‐old forests (53.3%) and ≥100‐year‐old forests (50.2%) both 1.5 times larger than ≤30‐year‐old forests (34.5%). Soil microbial biomass carbon and soil dissolved organic carbon increased by 21.0%‐33.6% and 60.3%‐87.7%, respectively, in response to natural and doubled litter inputs, while soil respiration increased linearly with corresponding increases in soil microbial biomass carbon and soil dissolved organic carbon. Natural and doubled litter inputs increased the total phospholipid fatty acid (PLFA) content by 6.6% and 19.7%, respectively, but decreased the fungal/bacterial PLFA ratio by 26.9% and 18.7%, respectively. Soil respiration also increased linearly with increases in total PLFA and decreased linearly with decreases in the fungal/bacterial PLFA ratio. The contribution of litter inputs to an increase in soil respiration showed a trend of total PLFA > fungal/bacterial PLFA ratio > soil dissolved organic carbon > soil microbial biomass carbon. Therefore, in addition to forest type and stand age, labile C availability and soil microorganisms are also important factors that influence soil respiration in response to litter inputs, with soil microorganisms being more important than labile C availability. Abstract : Soil respiration, labile C availability, and soil microorganisms (e.g., microbial quantity and community structure) were significantly influenced by litter inputs. The increase in soil respiration in response to litter inputs was closely related to labile C availability and soil microorganisms. Soil microorganisms had a greater effect than labile C availability influence soil respiration in response to litter inputs.